2022
DOI: 10.1111/jfpp.17087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroxypropyl methylcellulose, protein and fat on predicted glycemic index and antioxidant property of gluten‐free bread from rice flour

Abstract: Due to the lack of gluten, hydroxypropyl methylcellulose (HPMC), whey protein concentrate (WPC) and soy protein isolate (SPI) were fortified (4 g/100 g flour) into gluten‐free bread made from rice flour. The heteropolymer structure of HPMC and protein covered starch granules, resulting in a decrease in predicted glycemic index (pGI) of bread from 84.08 to 67.20–71.04. Addition of butter reduced the pGI to 73.55. By changing the baking mode from hot air baking to microwave baking and microwave‐hot air baking, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The use of HPMC and whey protein additionally enhanced the enhancement of antioxidant activity, as assessed by the DPPH experiment. [112] Instant rice White rice with different amylose content was cooked at different conditions [cooking temperature (82-90 • C), water: rice ratio (1.0-1.9-fold)].…”
Section: Rice Breadmentioning
confidence: 99%
“…The use of HPMC and whey protein additionally enhanced the enhancement of antioxidant activity, as assessed by the DPPH experiment. [112] Instant rice White rice with different amylose content was cooked at different conditions [cooking temperature (82-90 • C), water: rice ratio (1.0-1.9-fold)].…”
Section: Rice Breadmentioning
confidence: 99%
“…A study has shown that the addition of 1% HPMC leads to an improvement in the internal structure of bread and an increase in the level of porosity in GF bread based on rice and buckwheat flour (Baldino et al., 2018 ). In previous studies, the effects of HPMC on properties of GF bread from rice flour (Srikanlaya et al., 2022 ), different starch sources (rice flour or maize starch) (Belorio & Gómez, 2020 ), and potato starch (Chen et al., 2023 ) were studied. Pectin is another gum suggested for GF bread in which polysaccharide is derived from citrus peel or apple pomace.…”
Section: Introductionmentioning
confidence: 99%